Multi-dimensional epidemiology and informatics data on COVID-19 wave at the end of zero COVID policy in China - Yu, Xin-sheng; Tan, Shaoying; Tang, Wanting; Zhao, Fang-fang; Ji, Jie; Lin, Jianwei; He, Han-jie; Gu, Youxin; Liang, Jia-Jian; Wang, Meng; Chen, Yequn; Yang, Jiancheng; et al. (Frontiers in Public Health, 2024)
Background: China exited strict Zero-COVID policy with a surge in Omicron variant infections in December 2022. Given China's pandemic policy and population immunity, employing Baidu Index (BDI) to analyze the evolving disease landscape and estimate the nationwide pneumonia hospitalizations in the post Zero COVID period, validated by hospital data, holds informative potential for future outbreaks. Methods: Retrospective observational analyses were conducted at the conclusion of the Zero-COVID policy, integrating internet search data alongside offline records. Methodologies employed were multidimensional, encompassing lagged Spearman correlation analysis, growth rate assessments, independent sample T-tests, Granger causality examinations, and Bayesian structural time series (BSTS) models for comprehensive data scrutiny.Results: Various diseases exhibited a notable upsurge in the BDI after the policy change , consistent with the broader trajectory of the COVID-19 pandemic. Robust connections emerged between COVID-19 and diverse health conditions, predominantly impacting the respiratory, circulatory, ophthalmological, and neurological domains. Notably, 34 diseases displayed a relatively high correlation (r>0.5) with COVID-19. Among these, 12 exhibited a growth rate exceeding 50% postpolicy transition, with myocarditis escalating by 1708% and pneumonia by 1332%.In these 34 diseases, causal relationships have been confirmed for 23 of them, while 28 garnered validation from hospital-based evidence. Notably, 19 diseases obtained concurrent validation from both Granger causality and hospital-based data. Finally, the BSTS models approximated approximately 4,332,655 inpatients diagnosed with pneumonia nationwide during the two months subsequent to the policy relaxation.This investigation elucidated substantial associations between COVID-19 and respiratory, circulatory, ophthalmological, and neurological disorders. The outcomes from comprehensive multi-dimensional cross-over studies notably augmented the robustness of our comprehension of COVID-19's disease spectrum, advocating for the prospective utility of internetderived data. Our research highlights the potential of Internet behavior in predicting pandemic-related syndromes, emphasizing its importance for public health strategies, resource allocation, and preparedness for future outbreaks.